Pengembangan Panduan Ekstrakurikuler Pramuka Penegak Berbasis Kearifan Lokal pada SMA dan SMK Kota Salatiga - Listiarum, Febri; Jati, Dionisius Heckie Puspoko; Ningtyas, Ruth Siwi (Jayapangus Press, 2024)
The lack of appreciation among students at SMK Saraswati and SMA Kristen Satya Wacana in Salatiga towards instructors during lessons, coupled with the limited use of instructional materials (primarily textbooks), which are often solely held by educators and not accessible to students, prompted this research. This study aims to develop and evaluate a media-based Scout learning guide to enhance teaching effectiveness on Scout topics such as Scouting History, Morse Code, Semaphore, and Knotting. Currently, these topics lack sufficient media resources, leading to student difficulties in comprehending and mastering the material. This research employs the ADDIE model, comprising the stages of Analysis, Design, Development, Implementation, and Evaluation, to ensure a systematic and comprehensive development process. The instruments used include practicality questionnaires for Scout instructors and students, validation questionnaires from content and media experts, and tests assessing students' understanding of Scout topics. Validation results show that the guide received scores of 76% from media experts, 86% from content experts, and 74% from prospective users. Overall, the guide achieved an average score of 72% in terms of practicality and feasibility, indicating that it falls into the